Proanthocyanidin glycosides from the leaves of Quercus ilex L. (Fagaceae) (Tetrahedron Letters, 2009)
From the polar extracts of the leaves of Quercus ilex L., two new proanthocyanidin glycosides, namely afzelechin-(4a?8)-catechin-3-O-b-glucopyranoside (1) and afzelechin-(4a?8)-catechin-3-O-a-rhamnopyranoside (2), were isolated in addition to catechin (3), proanthocyanidin B3 (4), prodelphinidin C (5), dehydrodicatechin A (6), quercetin (7) and six known ﬂavonol glucosides with their acylated derivatives (8–13) and ellagic acid (14). The structures of all isolated compounds were established by spectroscopic means, mainly 1D and 2D NMR, as well as LC/MS and HR-MS spectrometric analyses. The absolute con- ﬁguration of compound 1 was determined by CD measurements. The proanthocyanidin glycosides are especially interesting, as they possess the sugar in the upper unit of the dimer, which is rare for this type of compounds.